Program KKN-T Peningkatan Kreativitas Mahasiswa Di Desa Paya Tusam : Penerapan Teknologi - Nuranisah (LKP KARYA PRIMA KURSUS, 2024)
The Thematic Real Work Lecture Program (KKN-T) is a community service activity that must be carried out by students to provide direct experience in applying the knowledge gained on campus. This activity aims to bring students closer to village communities, as well as develop students' practical abilities and character. One of the main focuses of KKN-T is to improve village development through the application of information and communication technology (ICT), which is expected to support economic growth and efficiency of community administration services. Even though several villages have begun to adopt digital technology, data processing and community services are still mostly done manually, causing delays in decision making. Therefore, the application of technology such as Machine Learning can be a solution to speed up and increase the accuracy of data processing, especially in determining recipients of social assistance and other administrative services. This research identifies obstacles in implementing technology in villages and provides technology-based solutions to overcome these problems. Through KKN-T activities in Paya Tusam Village, students provided education on the use of Machine Learning to increase the efficiency of administrative data processing. It is hoped that the results of this service will facilitate decision making and introduce villages to more modern technology, so that villages can develop and improve the quality of life of their people.